2009
DOI: 10.3109/08860220903180582
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative Glomerulonephritis Associated with Psoriasis Vulgaris

Abstract: Psoriasis is a hereditary, chronic inflammatory disorder of the skin. Generally, the psoriatic process is limited to the skin; however, internal organs such as the kidneys may be involved in the course. Several glomerular diseases have been distinguished due to renal histological findings of psoriatic patients to date. The underlying pathogenetic mechanisms of these associations remain unclear because of the limited number of cases. We report a case of primary membranoproliferative glomerulonephritis (MPGN) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…[40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children. [40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children. [40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children.…”
Section: Discussionmentioning
confidence: 87%
“…Prior small case studies have suggested that various types of GN, such as IgA nephropathy, membranous glomerulopathy and focal segmental glomerulonephritis, may be more likely to occur in patients with psoriasis. [40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children. 45 Moreover, because GN may progress to CKD or late stage CKD (ESRD) and the diagnosis of CKD is made on the basis of abnormal urinalysis and glomerular filtration rate results without knowledge of the specific cause, 46 we further investigated the relationship among GN, ESRD and psoriasis.…”
Section: Discussionmentioning
confidence: 87%
“…There are some reports that psoriasis is associated with glomerular disease. IgAN is the most frequent [6], and mesangial proliferative nephritis [7], amyloidosis [8], focal segmental glomerulosclerosis [9], minimal change disease [10], and membranoproliferative glomerulonephritis [11] have also been reported. However, as far as GPP is concerned, there are few reports of glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Nephropathy associated with psoriasis has been increasingly reported in recent years. These kidney diseases include IgA nephropathy [29, 30], MN [1114], membranoproliferative glomerulonephritis [31], focal segmental glomerulosclerosis [32], minimal change disease [33], AA-amyloidosis [34], and therapy-related tubular-interstitial alteration [26]. …”
Section: Discussionmentioning
confidence: 99%